(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
VANET is a novel way for fast-moving autos to connect. VANET provided traffic engineering, management, emergency information to avoid accidents, and other user applications. VANETs are similar to Mobile Ad hoc Networks (MANETs), but they have fast speeds, mobility, adequate storage and processing power, unexpected node density, difficult communication environments with limited connection lifespans, etc. Hence, VANET protocol testing needs realism. Vehicular Ad hoc Network (VANET) is a new communication paradigm that allows road network V2V and V2I communication (V2I). It supports traffic engineering, emergency information transfer, and other user applications. Vehicular networks distribute data about road traffic conditions to keep vehicles safe and efficient. VANET Applications’ characteristics—different network density, fast vehicle movement—make data dissemination difficult. Performance requirements determine these protocols’ vehicle area network applicability. Vehicles talking with each other and roadside units constitute Vehicular Ad-Hoc Networks (VANETs), a specific type of MANET (RSUs). VANETs allow safety, traffic management, and infotainment. Due to vehicle mobility and frequent network topology changes, VANETs have routing difficulties. This paper compares VANET routing protocols. . Simulations reveal that mobility pattern, network density, and traffic load affect protocol performance.